A Class of $q$-ary 2-IPP Codes (Journal of Informatics and Mathematical Sciences, 2013)
Sufficient conditions in terms of distance for the existence of binary 2-frameproof codes are obtained. A new class of $q$-ary 2-IPP codes has been explicitly constructed using latin square designs.
Keywords: Frameproof code; IPP code; Hash family; Latin square design